Study of Transient Stability with Battery Energy Storage Systems in Renewable Integrated Islanded Microgrid - Arif, Shaila; Aziz, Tareq (2017 IEEE International WIE Conference on Electrical and Computer Engineering (WIECON ECE), 2017)
The microgrid has become praise worthy concept due to a number of advantages. It can meet the increasing demand as well as can be a better solution for environmental pollution because of its renewable sources. A microgrid has to maintain voltage and frequency regulation in grid connected as well as in islanded mode. One of the challenges in islanded operation is transient stability. Battery energy storage system (BESS) is part and parcel of a renewable integrated microgrid. Impact of BESS on transient stability has been investigated in this study with IEEE 43 bus industrial test system. Results show that centralized placement offers improved transient stability than the distributed placement of BESS in microgrid.